5 questions with Brian Piper and Stephanie Geyer. Issue 7 (23rd March 2023) - Talarico, Donna
Abstract : Every now and then, the Recruiting and Retaining Adult Learners marketing column will profile a communications professional (or two) via a "5 questions with" feature. Sometimes the questions will vary from column to column based on current news and trends.